POD05 Impairment of vestibular memory in a patient with a right hippocampal lesion. Issue 11 (22nd October 2010) - Seemungal, B; Bronstein, A M; Chan, D; Kaski, D
Abstract : We assessed the vestibular memory of whole body rotations (via a computerised rotating chair in the dark) in a 65-year-old female patient with a right Hippocampal lesion. (1) The Egocentric Task (EGO): the subject actively returned themselves to their remembered start position in the dark using a chair-mounted joystick following an outbound passive rotation (30–180°). (2) The World Task (WORLD): This involved the same passive rotations as the EGO task but here the subject indicated their position relative to a large surrounding earth-fixed drum with images (only visible prior to rotations). A handheld miniature version of the drum was used by the patient to indicate their perceived position. A "go" signal delayed responses by 1, 4 or 8 s. The EGO task performance was at the upper limit of normal (r-square for response-stimulus angle=0.83) with no performance decrement at 4 s (r 2 =0.84) and only minimal worsening at 8 s delay (r 2 =0.67). The World task showed a moderate performance decrement at 1 s delay (r 2 =0.60) compared to the EGO task. Critically however, there was a significant performance decrement on going from a 1 s to a 4 s delay (4 s: r 2 =0.37; 8 s: r 2 =0.36). This suggests that short-term encoding, maintenance and retrieval of uncalibrated vestibular position signals (EGO task) are not reliant on right hippocampal function. In contrast, the rendition and maintenance of a calibrated (i.e., world-based) vestibular spatial memory may be reliant upon hippocampal mechanisms.